2023
DOI: 10.3390/polym15244733
|View full text |Cite
|
Sign up to set email alerts
|

Use of Bio-Epoxies and Their Effect on the Performance of Polymer Composites: A Critical Review

Monica Capretti,
Valentina Giammaria,
Carlo Santulli
et al.

Abstract: This study comprehensively examines recent developments in bio-epoxy resins and their applications in composites. Despite the reliability of traditional epoxy systems, the increasing demand for sustainability has driven researchers and industries to explore new bio-based alternatives. Additionally, natural fibers have the potential to serve as environmentally friendly substitutes for synthetic ones, contributing to the production of lightweight and biodegradable composites. Enhancing the mechanical properties … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 121 publications
(236 reference statements)
0
4
0
Order By: Relevance
“…Despite the challenges associated with this bioincorporation, existing studies on NFCs applications have shown positive enhancements in the mechanical properties through the addition of natural fibres. This improvement is attributed to the enhanced compatibility of natural fibres and the bio-matrix compared to traditional epoxy composites [102]. However, the adoption of fully bio-based composites in structural applications like the automotive industry is still limited.…”
Section: Nfcs and Automotive Industrymentioning
confidence: 99%
“…Despite the challenges associated with this bioincorporation, existing studies on NFCs applications have shown positive enhancements in the mechanical properties through the addition of natural fibres. This improvement is attributed to the enhanced compatibility of natural fibres and the bio-matrix compared to traditional epoxy composites [102]. However, the adoption of fully bio-based composites in structural applications like the automotive industry is still limited.…”
Section: Nfcs and Automotive Industrymentioning
confidence: 99%
“…Biobased epoxy resins offer several advantages over their petroleum-based counterparts. They can be derived from sustainable and renewable biomass sources, such as plant oils or sugars, reducing the reliance on fossil fuels and minimizing the carbon footprint associated with material production …”
Section: Introductionmentioning
confidence: 99%
“…They can be derived from sustainable and renewable biomass sources, such as plant oils or sugars, reducing the reliance on fossil fuels and minimizing the carbon footprint associated with material production. 14 Vegetable oils, such as soybean or linseed oil, are valuable renewable materials composed of triglycerides, which consist of glycerol and fatty acids. The epoxidation of these vegetable oils represents a significant advancement in functionalizing their double bonds, leading to the production of biobased monomers and resins.…”
Section: Introductionmentioning
confidence: 99%
“…For intumescent coatings, the different matrix materials used have very different properties [5][6][7][8]. Among them, epoxy resin as a kind of polymer thermosetting resin material has good film-forming, corrosion resistance, and electric insulation properties [9][10][11][12]. It also has many polar groups and highly active epoxy groups, and it can also maintain good adhesion with the surface of many materials at room temperature, such as steel, aluminum, and titanium alloy materials [13,14].…”
Section: Introductionmentioning
confidence: 99%